Once-Monthly Continuous Erythropoietin Receptor Activator (C.E.R.A.) in Patients with Hemodialysis-Dependent Chronic Kidney Disease: Pooled Data from Phase III Trials. Issue 4 (April 2016) - Locatelli, Francesco; Choukroun, Gabriel; Truman, Matt; Wiggenhauser, Alfons; Fliser, Danilo
Abstract Introduction Erythropoiesis-stimulating agents and iron are commonly used in patients with chronic kidney disease with the aim of correcting anemia and maintaining stable hemoglobin levels. We analyzed pooled data from 13 studies with similar designs included in the Umbrella Continuous Erythropoietin Receptor Activator (C.E.R.A.) program to investigate the effects of continuous erythropoiesis receptor activator in clinically relevant subgroups of patients with chronic kidney disease and to determine whether the efficacy and safety outcomes demonstrated in the overall chronic kidney disease population are maintained in specific subgroups. Methods Data from 13 Phase III trials set up with similar design were retrospectively pooled for this analysis. Patients with chronic kidney disease who had previously been receiving epoetin or darbepoetin were switched to continuous erythropoiesis receptor activator once-monthly after a 4- to 8-week screening period. Patients entered a 16-week continuous erythropoiesis receptor activator dose-titration period followed by an 8-week evaluation period. In total, 2060 patients were included in the analysis. Subgroups were defined based on: hemoglobin target range [lower (10.0–12.0 g/dL)/upper (10.5–13.0 g/dL)], gender (female/male), age (<65/≥65), baseline N-terminal pro-B-type natriuretic peptide levels (<5000/≥5000), cardiovascular risk factors (diabetes/cardiac/vascular/none). Results Across all subgroups analyzed, switching from shorter-acting erythropoiesis-stimulating agents to continuous erythropoiesis receptor activator once-monthly maintained stable hemoglobin concentrations in a high proportion of patients (78%), with only moderate hemoglobin fluctuations and a low number of dose changes. The safety profile across subgroups was as expected based on pre-existing risk factors; observed increases in adverse events were attributable to underlying risk factors rather than study drug. Conclusions This retrospective analysis of 13 trials showed that continuous erythropoiesis receptor activator once-monthly maintained stable hemoglobin levels across a number of clinically relevant patient subgroups, including those with higher inherent cardiovascular risk. The safety profile was consistent with that previously established in the chronic kidney disease population. ClinicalTrials.gov identifiers NCT00413894/NCT00545571/NCT00517413/NCT00560404/NCT00882713/NCT00550680/NCT00576303/NCT00660023/NCT00717821/NCT00642850/NCT00605293/NCT00661505/NCT00699348. Funding F. Hoffmann-La Roche Ltd, Basel, Switzerland.